Therapeutic efficacy of ozone insufflations in alleviating endometritis in cows - Patra, Bijay Kumar; Nath, Indramani; Nayak, Kuresh Kumar; Mishra, Rajshree; Mishra, Chinmay; Biswal, Shuvranshu Shek har; Sahoo, Anjan Kumar; Parida, Sunil Manohar (The Indian Journal of Animal Reproduction, 2023)
The present investigation was carried out to study the effect of intrauterine ozone insufflation alone or in combination with cephalexin in treating the postpartum clinical endometritis in dairy cows.  A total number of fourteen postpartum clinical endometritic cows selected after screening were allotted randomly into 2 equal groups (n=7). The Group I & II cows were intrauterinely administered with ozone insufflations either alone or in combination with cephalexin (Lixen-IU®). Seven postpartum normal cyclic animals were taken as control. Following treatment the overall reduction in combined mucous character and odour both in group I (82.04%) and group II (87.25%) were similar and highly significant (p
Keywords: Bacterial load; Endometritis; Ozone therapy